Magnetic resonance imaging findings of core muscle injuries in high level athletes - Dekker, T. M.; Uppstrom, T. J.; Emerson, C. P.; Vickers, R. F.; Greditzer, H. G. (Current Sports Medicine Reports, 2021)
Core muscle injuries are common injuries in athletes involved in high speed side-to-side acceleration movements. The term core muscle injury encapsulates several different injuries that occur in the pelvic region that have similar presentations. Along with a good history and physical examination, magnetic resonance imaging (MRI) can be a helpful tool in the diagnostic process. Correct orientation and protocols are needed to show the correct anatomy with an MRI. Furthermore, to determine the exact etiology of the core muscle injury, it is important to know which structures are likely to be involved and be able to recognize the patterns of injury on imaging.